2015
DOI: 10.1098/rstb.2013.0382
|View full text |Cite
|
Sign up to set email alerts
|

Proxy comparison in ancient peat sediments: pollen, macrofossil and plant DNA

Abstract: We compared DNA, pollen and macrofossil data obtained from Weichselian interstadial (age more than 40 kyr) and Holocene (maximum age 8400 cal yr BP) peat sediments from northern Europe and used them to reconstruct contemporary floristic compositions at two sites. The majority of the samples provided plant DNA sequences of good quality with success amplification rates depending on age. DNA and sequencing analysis provided five plant taxa from the older site and nine taxa from the younger site, corresponding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 44 publications
2
67
1
3
Order By: Relevance
“…The macrofossil record is often dominated by the aquatic and wetland plants growing in and around the lake, and terrestrial taxa are often under‐represented (Birks, ). sed aDNA seems to have a similar source of origin to macrofossils (Jørgensen et al ., ; Pedersen et al ., ; Alsos et al ., ; Parducci et al ., ). To date, only a few studies have focused on the release and deposition of DNA in the environment (Poté et al ., , ; Pietramellara et al ., ; Barnes & Turner, ), and therefore much remains unknown about the ecology of the DNA – for example, all processes occurring from source to deposition (taphonomy).…”
Section: Sources Of Pollen Macrofossils and Dnamentioning
confidence: 97%
“…The macrofossil record is often dominated by the aquatic and wetland plants growing in and around the lake, and terrestrial taxa are often under‐represented (Birks, ). sed aDNA seems to have a similar source of origin to macrofossils (Jørgensen et al ., ; Pedersen et al ., ; Alsos et al ., ; Parducci et al ., ). To date, only a few studies have focused on the release and deposition of DNA in the environment (Poté et al ., , ; Pietramellara et al ., ; Barnes & Turner, ), and therefore much remains unknown about the ecology of the DNA – for example, all processes occurring from source to deposition (taphonomy).…”
Section: Sources Of Pollen Macrofossils and Dnamentioning
confidence: 97%
“…Due to the large degree of concurrence of taxa detected as sedaDNA and macrofossils (Table 2), one may argue that the proxies show overlap rather than being complimentary as suggested by others (Jørgensen et al, 2012;Parducci et al, 2013Parducci et al, , 2015Pedersen et al, 2013).…”
Section: Added Understanding Of Vegetation By Sedadna Compared To Onlmentioning
confidence: 99%
“…For example, while sedaDNA has lower taxonomic resolution than macrofossils for the important family Salicaceae, it reveals taxa that were not present as macrofossils, such as Huperzia and several species within the Poaceae, taxa less commonly recorded in macrofossil studies. Previous sedaDNA studies from the Arctic are characterized by less overlap between sedaDNA and macrofossils (10 -35%: Jørgensen et al, 2012;Parducci et al, 2012aParducci et al, , 2012bParducci et al, , 2013Parducci et al, , 2015Pedersen et al, 2013;56%: Porter et al, 2013).…”
Section: The Capacity Of Sedadna To Provide a Record Of Past Floramentioning
confidence: 99%
See 1 more Smart Citation
“…First used in studies of palaeo-biodiversity (Herbert et al 2003), this approach has been shown to track the variation in the abundance of plants and domestic animals over the last six millennia, enabling the reconstruction of human impacts on alpine lakes through time (Giguet-Covex et al, 2014). The peats contained within many floodplain fills are also potential carriers for sedaDNA (Rawlence et al, 2014;Parducci et al, 2015). At present there are few studies but an ongoing research in Arctic Norway has recovered the sedaDNA of over species from small valley-floor ponds in the Veranger peninsula (Clarke et al in prep.).…”
Section: Accepted Manuscriptmentioning
confidence: 99%